2013
DOI: 10.3747/pdi.2012.00009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration Characteristics of Glucose Polymers with Low Polydispersity

Abstract: Glucose polymers with low polydispersity are effective osmotic agents in a rabbit model. The low-Mw polymer was more effective at generating UF and had a higher UF efficiency, but those results came at the expense of the polymer being more readily absorbed from the peritoneal cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In contrast, compared with 7.5% icodextrin, 7.5% 19 kDa glucose polymer of low polydispersity achieved both lower net UF and lower carbohydrate absorption. These theoretical results are qualitatively comparable to those we reported previously based on experiments in a rabbit model (9). Decreasing the polydispersity of either glucose polymer without altering the weight-average molecular weight had a minor effect on net UF, but resulted in substantially lower carbohydrate absorption.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, compared with 7.5% icodextrin, 7.5% 19 kDa glucose polymer of low polydispersity achieved both lower net UF and lower carbohydrate absorption. These theoretical results are qualitatively comparable to those we reported previously based on experiments in a rabbit model (9). Decreasing the polydispersity of either glucose polymer without altering the weight-average molecular weight had a minor effect on net UF, but resulted in substantially lower carbohydrate absorption.…”
Section: Resultssupporting
confidence: 92%
“…Our experimental results were obtained in a rabbit model that we have previously used to study glucose polymer osmotic agents (9). The current experiments were similar in design, except that the dwell was extended to 8 hours from 4 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8D). Ultrafiltration of the dialyzed sample revealed that the activity was contained in the .10 kDa fraction, suggesting that the relatively imperfect molecular cutoff of dialysis bags [40] allowed larger, active molecules to leak into the DLE. The DLE preparation was evaluated for cytokine contamination and found to be negative for IFN-g, IL-1a, IL-1b, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12, IL-13, IL-17A, and TNF-a (not shown).…”
Section: The Active Fraction Of Dle Does Not Contain Antigen Contaminmentioning
confidence: 99%
“…The polydispersity for icodextrin is reported to be 2.6. 130 Using the three-pore model for theoretical calculations, investigators evaluated the use of glucose polymers with low polydispersity in rabbit models. They were able to show long-dwell PD fluids containing 11% 18-19 kDa glucose polymers with low polydispersity can provide higher UF without higher carbohydrate absorption.…”
Section: Polyglucose Solutionsmentioning
confidence: 99%